2007
DOI: 10.1111/j.1439-0442.2007.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Nuclear DNA Integrity of Frozen–Thawed Spermatozoa from Thai AI Swamp Buffaloes (Bubalus bubalis)

Abstract: In this study, we investigated the susceptibility of frozen-thawed swamp buffalo sperm nuclear DNA to undergo controlled acid-induced denaturation in situ, as analysed by flow cytometry, and aimed to correlate the results with sperm head morphology over three seasons in tropical Thailand. Artificial insemination (AI) doses (n = 218) from 18 AI buffalo sires, prepared between 1980 and 1989 and 2003 and 2005, were tested and compared among three seasons, the rainy season, July-October; winter, November-February;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…These results suggest that postthaw sperm parameters, especially PMI and DNA integrity of sperm, are reliable indicators of fertility, as has been suggested previously (27,28). In addition, this is supported by the highest fertility rate noticed in the present study for bulls KWC-24, KWC-25, and KWC-28 which revealed the highest DNA integrity of spermatozoa.…”
Section: Discussionsupporting
confidence: 77%
“…These results suggest that postthaw sperm parameters, especially PMI and DNA integrity of sperm, are reliable indicators of fertility, as has been suggested previously (27,28). In addition, this is supported by the highest fertility rate noticed in the present study for bulls KWC-24, KWC-25, and KWC-28 which revealed the highest DNA integrity of spermatozoa.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, DNA fragmentation assay based on TUNEL staining could not identify any significant changes in nuclear structures of cryopreserved buffalo sperm. A number of previous studies also reported that DNA integrity was unaffected during freezing and thawing of sperm in swamp buffalo (Koonjaenak et al. 2007), human (Duru et al.…”
Section: Discussionmentioning
confidence: 92%
“…In humans, and only under certain conditions of assessment of fertility (assisted reproductive technology procedures), males with semen samples with more that 30% DNA fragmentation index were considered unable of establishing pregnancy. 103 In animals, where SCSA is the most widespread method to assess chromatin integrity among domestic animals, [104][105][106] particularly related to processed semen (including storage and cryopreservation), there is a relationship between chromatin damage and fertility, but thresholds are far from established with certainty. 11 Another parameter indicated by SCSA is the ratio of spermatozoa with high green fluorescence.…”
Section: Sperm Intactnessmentioning
confidence: 99%